(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Oil sector is one of the most important sectors affecting the ecological balance, as activity contributes to the oil companies to influence their working environment, both during the oil exploration and extraction process or during transfer from one place to another process. We will try through this research put an environmental audit program proposal takes into account all the financial aspects, commitment and performance, according to the laws and regulations and agreements as well as relevant international standards, was based on research on the premise that the development of an environmental proposal auditing program that includes environmental controls on oil industry phases which helps reduce or minimize environmental pollutants By identifying environmental violations for companies as well as a reduction in developments in the production, affecting the company’s revenue losses.